Analysis Bibliometric SME Internationalization Process: Uppsala Model - Ambarwati, Titiek; Sudarmiatin, Sudarmiatin; Sumarsono, Hadi (International Journal of Science, Technology & Management, 2023)
A bibliometric analysis centered on the internationalization process of small and medium-sized firms (SMEs) with the Uppsala Model is presented in this article. The Uppsala model, which was first published in 1977, explains the process by which companies become internationalized. This model has been the subject of extensive research and development over the years. The literature on SME internationalization is investigated in this analysis, with a specific focus on the keywords "Uppsala model," "SMEs," "internationalization," and "export." This study use of bibliometric techniques, such as network visualization and density visualization, to uncover patterns in research and author collaborations. The findings underline the usefulness of the Uppsala model in the process of comprehending the internationalization of SMEs and bring attention to aspects such as resources, international plans, and dynamic capabilities that affect this procedure. This study contributes to the current body of information on the internationalization of SMEs and lays the groundwork for further investigation in this area.